Cost-Effectiveness Analysis of Early Reading Programs: A Demonstration With Recommendations for Future Research. Issue 1 (2nd January 2016) - Hollands, Fiona M.; Kieffer, Michael J.; Shand, Robert; Pan, Yilin; Cheng, Henan; Levin, Henry M.
Abstract: We review the value of cost-effectiveness analysis for evaluation and decision making with respect to educational programs and discuss its application to early reading interventions. We describe the conditions for a rigorous cost-effectiveness analysis and illustrate the challenges of applying the method in practice, providing examples of programs for which we have estimated costs, but find effectiveness data lacking in comparability. We provide a demonstration of how cost-effectiveness analysis can be applied to two early reading programs: the Wilson Reading System and Corrective Reading. We use existing effectiveness data from an experimental evaluation in which the programs were implemented under similar conditions and the use of common outcomes measures for both programs yielded data that are comparable. We combine these data with cost data we collected using the ingredients method to calculate cost-effectiveness ratios for the alphabetics domain. A complete picture of the relative cost-effectiveness of each program could be provided if effectiveness metrics were available for fluency, vocabulary, and comprehension. We highlight the obstacles to applying cost-effectiveness analysis more frequently and recommend strategies for improving the availability of the requisite data.